Proximate and socio-economic determinants of under-five mortality in Benin, 2017/2018 - Yaya, Sanni (BMJ Glob Health, 2020)
BACKGROUND: Globally, under-five mortality has declined significantly, but still remains a critical public health problem in sub-Saharan African countries such as Benin. Yet, there is no empirical information in the country using a nationally representative data to explain this phenomenon. The aim of this study was to examine how proximate and socio-economic factors are associated with mortality in under-five children in Benin. METHODS: We analysed data of 5977 under-five children using the 2017 to 2018 Benin Demographic and Health Surveys. Multivariable hierarchical logistic regression modelling technique was applied to investigate the factors associated with under-five mortality. The fit of the models were assessed using variance inflation factor and Pseudo R(2). Results were reported as adjusted odds ratios (aORs). All comparisons were considered to be statistically significant at p<0.05. RESULTS: The study revealed an under-five mortality rate of 96 deaths per 1000 live births in Benin. Regarding the socio-economic determinants, the risk of death was found to be higher in children born in the Plateau region (aOR=3.05; 95% CI: 1.29 to 7.64), in rural areas (aOR=1.45; 95% CI: 1.07 to 1.98) and children with ≥4 birth rank and >2 years of birth interval (aOR=1.52; 95% CI: 1.07 to 2.17). Among the proximate determinants, we found the probability of death to be higher in children whose mothers had no postnatal check-up (PNC) visits after delivery (aOR=1.79; 95% CI: 1.22 to 2.63), but there was no significant association between individual-level/household-level factors and under-five mortality. CONCLUSION: This study has established that socio-economic and proximate factors are important determinants of under-five mortality in Benin. Our findings have shown the need to implement both socio-economic and proximate interventions, particularly those related to PNC visits when planning on under-five mortality. To achieve this, a comprehensive, long-term public health interventions, which consider the disparity in the access and utilisation of healthcare services in Benin are key.